Perspectives on LHC Physics - Kane, Gordon; Pierce, Aaron (World Scientific Publishing Co., 2008)
The Large Hadron Collider (LHC), located at CERN, Geneva, Switzerland, is the world's largest and highest energy and highest intensity particle accelerator. Here is a timely book with several perspectives on the hoped-for discoveries from the LHC. This book provides an overview on the techniques that will be crucial for finding new physics at the LHC, as well as perspectives on the importance and implications of the discoveries. Among the accomplished contributors to this book are leaders and visionaries in the field of particle physics beyond the Standard Model, including two Nobel Laureates (Steven Weinberg and Frank Wilczek), and presumably some future Nobel Laureates, plus top younger theorists and experimenters. With its blend of popular and technical contents, the book will have wide appeal, not only to physical scientists but also to those in related fields. The LHC - A "Why" Machine and a Supersymmetry Factory (G Kane) Dark Matter at the LHC (A Pierce) LHC's ATLAS and CMS Detectors (M Spiropulu & S Stapnes) Understanding the Standard Model, as a Bridge to the Discovery of New Phenomena at the LHC (M L Mangano) Thoughts on a Long Voyage (L Susskind) The "Top Priority" at the LHC (T Han) LHC Discoveries Unfolded (J Lykken & M Spiropulu) From BCS to the LHC (S Weinberg) Searching for Gluinos at the Tevatron and Beyond (J Alwall et al.) Naturally Speaking: The Naturalness Criterion and Physics at the LHC (G F Giudice) Prospects for Higgs Boson Searches at the LHC (K Jakobs & M Schumacher) A Review of Spin Determination at the LHC (L-T Wang & I Yavin) Anticipating a New Golden Age (F Wilczek) Strongly Interacting Electroweak Theories and Their Five-Dimensional Analogs at the LHC (A Pomarol) How to Find a Hidden World at the LHC (J D Wells) B Physics at LHCb (M P Altarelli & F Teubert) The LHC and the Universe at Large (P Binétruy)